Numerical study of profiled conformal cooling channels for cooling time reduction in injection mould tools. (2015) - Altaf, Khurram; Rani, Ahmad Majdi bin Abdul
In injection moulding, cooling time for polymer and process thermal management are critical issues having key effects on process cycle times. In the conventional injection moulds, cooling channels have circular cross-section due to the manufacturing technique of drilling. In a circular channel, there can be a problem that the distance from the edges of channel to the cavity is not constant and is variable even for conformal channels. In this study, injection mould designing and thermal simulations are performed and a comparison is presented between circular cooling channel mould with profiled cooling channel mould. The objective for the current study is to propose a new design of cooling channel for the reduction in the cooling time for injection moulding process. Thermal simulations indicate that profiled channels were dissipating heat more effectively than circular channels and hence profiled channels would have a reduced cooling time than circular channels.